The impact of taxes and transfer payments on the distribution of income: A parametric comparison - Samuel R. Dastrup; Rachel Hartshorn; James B. McDonald (Luxembourg Income Study (LIS), 2005)
The Luxembourg Income Study data is used to explore the impact of taxes and transfer payments on the distribution of income across thirteen countries for different years. The five-parameter generalized beta distribution and ten of its special cases are considered as models for the size distribution of income. Maximum likelihood methods are used to estimate the model with corresponding measures of goodness of fit and inequality reported. These results identify the best-fitting two, three, and four- parameter models as well as describe the inter-temporal patterns of inequality corresponding to earnings, total income, and disposable income. A general pattern of increasing inequality is observed for almost all countries considered along with significantly different distributional impacts of taxes and transfer payments across countries.
Keywords: 330; Einkommensverteilung; Gini-Koeffizient; Disparitätsmaß; Steuerbelastung; Schätzung; OECD-Staaten